Consistency of toddler engagement across settings - Aguiar, C.; McWilliam, R. A. (Early Childhood Research Quarterly, 2013)
This study documented the consistency of child engagement across two settings, toddler child care classrooms and mother-child dyadic play. One hundred twelve children, aged 14-36 months (M=25.17, SD=6.06), randomly selected from 30 toddler child care classrooms from the district of Porto, Portugal, participated. Levels of engagement were coded, and sophisticated engagement, but not nonengagement, was consistent across settings. Consistency in children's sophisticated engagement was primarily accounted for by chronological age. Children spent more time in sophisticated behaviors and less time nonengaged during mother-child dyadic play than in center-based child care. For sophisticated engagement, effects of child predictors were stronger than effects of environmental features; whereas for nonengagement, effects of environmental features were stronger than effects of child predictors. Findings suggest children's sophisticated engagement may be generalizable across settings, as a function of age, whereas their nonengagement is most likely context dependent.